The petrotype of the Neoarchaean Atamansky granite complex (Kursk block, Sarmatia): geochemistry, geochronology, and isotopic taxonomy (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The Atamansky complex, as well as most early Precambrian magmatic and metamorphic complexes of the Voronezh Crystalline Massif, has no modern, accurate geochronological data and geochemical characteristics. The aim of the study is to provide the most complete description of the petrotype of the Atamansky massif in the similarly-named complex. Methodology: The composition of petrogenic, small, and rare elements in the rocks of the Atamansky massif was determined, their Sm-Nd and Lu-Hf isotopy was studied, local mineral analyses were carried out, the age of the rocks was determined using the U-Pb method applied to zircon. Results and discussion: The Atamansky massif, which is a petrotype of the Atamansky complex in the Kursk block (Sarmatia), is radically different from the rest of the early Precambrian granitoids of the Voronezh Crystalline Massif. Granitoids of the Aramansky complex are 2.61 billion year old, they are rich in silica, have low calcium and strontium content, high iron content, and deep europium anomalies. The Lu-Hf isotopic composition of zircon and Sm-Nd isotopy of bulk samples indicate a long crustal history of protoliths and heterogeneity of Paleoarchean crustal sources. Conclusions: The Atamansky granite forms a locally manifested unified volcanic-plutonic association with high-silica rhyolites of the Lebedinskaya Formation. The granite was formed during high-temperature shallow melting in an intraplate environment as a result of the rise of the mantle plume and the introduction of basaltic magma into the crust, which served as heat sources.
Keywords: Kursk block; granite; U-Pb isotopic age; isotopic taxonomy; sources of melts; petrotype